Study of the LMNA 1908 C/T gene polymorphism in type 2 diabetic Egyptians with vascular complications - Heba Mostafa; Manal Eldeeb; Ahmed Hamdy; Rasha M Abdel Samie; Badawy El-Kholy; Nahla Fawzy; Ahmed Eltaweel; Nahed M Ibrahim (SpringerOpen, 2015)
Aims/introduction Vascular complications are the main cause of morbidity and mortality in type 2 diabetic patients. Genetic susceptibility is associated with the evolution of diabetic complications. One such gene is the lamin A and C gene located on chromosome 1q21, a susceptibility locus for type 2 diabetes mellitus, and encodes nuclear lamins A and C. The LMNA 1908 C/T polymorphism has been reported to be associated with dyslipidemia, metabolic syndrome, and obesity, suggesting that this polymorphism increases the risk of atherosclerosis and vascular disease. The present study aims to elucidate the association between the LMNA 1908 C/T single nucleotide polymorphism and the prevalence of vascular complications in a sample of type 2 diabetic Egyptian patients. Materials and methods Genomic DNA from 47 type 2 diabetic patients with vascular complications and 20 control participants was analyzed for the LMNA 1908 C/T polymorphism using PCR-RFLP. Results Carriers of the LMNA 1908 T-allele showed a significantly higher prevalence in patients with diabetic nephropathy than carriers of the C-allele (P < 0.05). Multiple regression analysis showed that the LMNA 1908 T-allele tended to be independent risk factor for diabetic nephropathy (P = 0.012, odds ratio = 5.460). Conclusion The findings of this study suggest that the LMNA 1908 C/T single nucleotide polymorphism is associated with the development of diabetic nephropathy in Egyptian type 2 diabetic patients.